Educational Management Strategies to Address Information Security Challenges in the Use of Social Media in Learning Environments - Ahmad Jauhari Hamid Ripki (Jurnal Minfo Polgan, 2023)
With the advancement of information technology, social media has become an integral part of daily life, including in the field of education. However, the use of social media in the learning environment is not exempt from information security challenges that can impact the effectiveness and sustainability of the learning process. This research aims to examine educational management strategies to address information security challenges in the use of social media in learning environments. The study employed an extensive review of existing literature through qualitative analysis to gain a comprehensive insight into the subject, covering the period from 2017 to 2023. The study's findings indicate that, in addressing the complexity of information security challenges related to the use of social media in learning environments, a holistic educational management approach is necessary. Awareness of risks, the development of clear policies, the selection of secure technologies, external collaboration, and continuous monitoring are key factors in creating a safe and innovative learning environment.